2021
DOI: 10.3390/vetsci8120300
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Heart Scale for the Brittany Spaniel: Breed-Specific Range and Its Correlation with Heart Disease Assessed by Clinical and Echocardiographic Findings

Abstract: The vertebral heart scale (VHS) was proposed by Buchanan and Bucheler as an objective method for estimating heart size in dogs. However, several studies have reported significant variation between breeds. The purpose of this retrospective study was to evaluate the VHS and to suggest a useful upper limit for normal heart size in Brittany Spaniels. The VHS was measured using a right lateral view in twenty-eight normal dogs and fifteen dogs with myxomatous mitral valve disease. The mean ± SD (standard deviation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Only one right lateral radiography was used for both VHS and VLAS measurements. However, most of the previous studies have used the same recumbence for analysis in both healthy and diseased dogs 8,13,23,24,27 . Moreover, some studies reported no significant differences between left and right recumbence 7,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one right lateral radiography was used for both VHS and VLAS measurements. However, most of the previous studies have used the same recumbence for analysis in both healthy and diseased dogs 8,13,23,24,27 . Moreover, some studies reported no significant differences between left and right recumbence 7,28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the previous studies have used the same recumbence for analysis in both healthy and diseased dogs. 8,13,23,24,27 Moreover, some studies reported no significant differences between left and right recumbence. 7,28 Second, our population was overrepresented by Maltese dogs.…”
Section: Discussionmentioning
confidence: 99%
“…VHS 21 has been used as one of the standard methods to evaluate cardiac silhouette size on thoracic radiographs for animals. However, there are two major issues with the calculation of VHS.…”
Section: Methodsmentioning
confidence: 99%
“…In 1995, Buchanan and Bücheler described the vertebral heart score (VHS) as an objective method for assessing heart size 8 . Since then, a number of studies have evaluated its reliability by assessing the intra‐ and inter‐observer agreement, the effects of sex, breathing, cardiac cycle, body condition score, and recumbency on the measurements, and determined indices for individual breeds that tend to deviate from the initially reported cut‐off values 9–25 . VHS is very useful in clinical practice because it is relatively simple to determine at initial and follow‐up examinations 19,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Since then, a number of studies have evaluated its reliability by assessing the intra-and inter-observer agreement, the effects of sex, breathing, cardiac cycle, body condition score, and recumbency on the measurements, and determined indices for individual breeds that tend to deviate from the initially reported cut-off values. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] VHS is very useful in clinical practice because it is relatively simple to determine at initial and follow-up examinations. 19,26,27 However, some limitations exist, including the difficulty of determining VHS in patients with spondylosis deformans, reduced intervertebral disc spaces, or vertebral malformations such as hemivertebrae, butterfly vertebrae or wedge vertebrae.…”
Section: Introductionmentioning
confidence: 99%